2021
DOI: 10.34133/2021/9870879
|View full text |Cite
|
Sign up to set email alerts
|

Hunting Sodium Dendrites in NASICON-Based Solid-State Electrolytes

Abstract: NASICON- (Na superionic conductor-) based solid-state electrolytes (SSEs) are believed to be attracting candidates for solid-state sodium batteries due to their high ionic conductivity and prospectively reliable stability. However, the poor interface compatibility and the formation of Na dendrites inhibit their practical application. Herein, we directly observed the propagation of Na dendrites through NASICON-based Na3.1Zr2Si2.1P0.9O12 SSE for the first time. Moreover, a fluorinated amorphous carbon (FAC) inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 48 publications
2
64
0
Order By: Relevance
“…As the scanning rate increases, the reaction deviates more from the equilibrium state, resulting in an increase in overpotential, which shifts the oxidation peak to a positive potential. The relationship between scan rate and current density could be determined by the power-law as follows: in which b = 1 and 0.5 indicate a capacitance- and diffusion-controlled process of electrode. As we can see from Figure b, the obtained b value is 0.889, indicating that storing Na + in PL-600 is dominated by capacitive process.…”
Section: Resultsmentioning
confidence: 99%
“…As the scanning rate increases, the reaction deviates more from the equilibrium state, resulting in an increase in overpotential, which shifts the oxidation peak to a positive potential. The relationship between scan rate and current density could be determined by the power-law as follows: in which b = 1 and 0.5 indicate a capacitance- and diffusion-controlled process of electrode. As we can see from Figure b, the obtained b value is 0.889, indicating that storing Na + in PL-600 is dominated by capacitive process.…”
Section: Resultsmentioning
confidence: 99%
“…The assembled Na symmetric batteries exhibited a high CCD of 1.0 mA cm −2 . [117] Similar strategies include the formation of the polymer layer, [113,118] metal oxide, [59,119] AlF 3 , [120] and other carbonaceous materials [121] as interlayers between NaSICON electrolyte and Na metal were found to improve the wetting and compatibility of NaSICON electrolyte with metallic Na.…”
Section: Anode/nasicon Interfacementioning
confidence: 99%
“…The strategy (2) involves multiple methods, including the implementation of Na-based composite anodes [42], surface coatings (i.e., Sn, TiO 2 , AlF 3 , PVDF, etc.) [13,14,[43][44][45][46][47], and bulk doping of NZSP [48][49][50]. Zhou et al demonstrated that heating NZSP over 300 • C results in the in situ formation of a thin interfacial interlayer with good molten Na wettability (Figure 2a,b) [41].…”
Section: All-solid-state Sodium-metal Batteriesmentioning
confidence: 99%
“…In recent years, all-solid-state SMBs have received considerable interest due to their attractive safety from the use of nonflammable and thermally stable solid electrolytes (SE), and potentially high energy density from the use of Na metal anodes and high-voltage cathodes [2,[9][10][11][12]. However, they suffer from the same or even more severe Na|SE wetting issues since they are supposed to run at room or ambient temperatures below the melting point of Na at 98 • C. The poor Na|SE contact will lead to large interfacial resistances and inhomogeneous Na stripping/plating morphologies, resulting in dendrite growth and eventually cell short circuits [13][14][15]. To tackle this issue, wetting-enhancement-based therapies have been extended from molten SMBs to all-solid-state SMBs.…”
Section: Introductionmentioning
confidence: 99%